The Well-Being of the Academic Community During the COVID-19 Pandemic - Przyborowska, Beata; Błajet, Piotr; Fopka-Kowalczyk, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Since 2020, the entire world has been struggling with the SARS-CoV-2 pandemic. The constant increase in the number of sick and dying people and the need for quarantine and social distancing have significantly affected the functioning of people, regardless of their background, age and activities. This article aims to examine the level of well-being among the academic community of Nicolaus Copernicus University in Poland based on the concept of Ken Wilber. To this end, a self-administered questionnaire was developed to assess the overall well-being, as well as the respondents’ well-being related to emotions, relationships, health, and the sense of security and satisfaction experienced during the pandemic. A total of 1,164 university employees and 1,601 doctoral and other students participated in the study. Teachers represented the highest levels of overall well-being, scoring higher than doctoral students and undergraduates. The older the respondents, the higher the perceived levels of overall well-being. These findings indicate that doctoral and other students are struggling with reduced levels of well-being and a reduced sense of the quality of life, displaying signs of emotional difficulties, anxiety and fear.